Internet distribution of luxury products : is there a deluxe version of EU competition law? - Kunda, Ivana (Array, 2019)
Owing to its particular features, the market of luxury goods is a point of interest to lawyers as much as to other professions such as economists or sociologists. These features play an important role in legal regulation of the market. While the starting point is competition law, the assessment of anticompetitive conduct under Article 101 of the TFEU cannot be complete without resorting to intellectual property law policies and rules. With the rise of the importance of internet sales, novel issues have been put before the competition authorities and reviewing courts, such as legality of various types of online restrictions in the selective distribution systems. Employing a combined IP law and competition law approach to these issues, this paper offers insights and comments on EU case law, with primary focus on the recent CJEU judgment in Coty. The intricacies of the interplay among different competition law rules and exemptions is particularly evidenced in this case. However, limited by its fact-pattern, the Coty judgment may serve as a clarification about the deluxe competition law treatment only of certain online sale prohibitions within the SDSs, while there will certainly be continuing discussions and national case law developments on other internet related competition law restrictions awaiting further elucidations by the CJEU.